Cybersecurity in Smart Railways: Exploring risks, vulnerabilities and mitigation in the data communication services - Tiago Fernandes; João Paulo Magalhães; Wellington Alves (Green Energy and Intelligent Transportation)
Smart trains and railways are gaining increasing significance in major global cities as they offer solutions to issues like traffic congestion and environmental pollution. Technological advancements have facilitated the transition from conventional systems to more advanced, highly efficient, and personalized railway systems. However, the complexity of these systems presents challenges, especially in terms of reliability, interoperability security, and privacy. With the potential vulnerability of railway systems to cyberattacks, it becomes crucial for these emerging smart systems to establish stringent privacy and security requirements. Cybersecurity is a key requirement to enable railways to deploy and take advantage of the full extent of a connected, digital environment. This research explores the cybersecurity landscape within Smart Railways aiming to identify potential threats and associated risks on these systems, focusing on analyzing the current literature related to Smart Railways and cybersecurity aspects, then listing key technologies used by smart systems, and finally proposing an illustration of use cases application to call attention to the impact of attacks, providing then as a set of good practices that must be followed to reduce risks and to the safeguard the operability for Rail Transportation. The research findings suggest that over the last few years, there has been a significant increase in research activity in this area, indicating a growing recognition of the importance of cybersecurity in the railway industry. The results also pointed out several gaps related to this topic, namely the lack of standardization in cybersecurity practices and limited consideration of human factors that can impact cybersecurity.